Implementación de una página Web con gastronomía peruana en el cantón Quevedo, Ecuador Año 2019 - Juárez Alarcón, Luis Rogerio (2019)
This research project developed in the Quevedo Canton, province of Los Ríos, the general objective is to create Peruvian gastronomy’s web page to offer this kind of dishes with delivery’s service and like this increase positioning of Peruvian gastronomy in the local market. Achieving optimal results for the creation of the webpage with the domain www.cuperchef.com. The design is interactive, professional and attractive to users that surfing in the webpage. Three specific objectives were considered, as follows. The first objective measured the level of acceptance of the webpage through the application of a survey with ten questions, age, sector where live, if would agree whit the creation Peruvian gastronomy´s webpage, if you have tasted Peruvian food once time, which Peruvian dishes would you like to get in the Quevedo canton, average spending, frequency of purchase, if you utilize digital’s platform, the cellphone apps that use to buy food, if you would buy lunch in digital platform whit service delivery and if you know some Peruvian restaurant in Ecuador. The second objective is the identification of the contents through the dishes’ pictures that cooked, cookbook, the design of logo in the app Tailor Brands and finally the third objective that is the webpage´s design it achieved in the hosting server Goo Daddy and the app Wordpress through template pre - established and design´s functions. To conclude that creation of webpage has a design interactive, useful and it to connect with social networks more used in the last time, just like that would improve the approach of Peruvian gastronomy in the Quevedo canton. Key words: webpage, food, Peruvian, delivery, dishes,